Friday

December 19, 2014

December 19, 2014

Posted by **LEON** on Saturday, November 13, 2010 at 1:16am.

- math calculus -
**Damon**, Saturday, November 13, 2010 at 4:44amx(3y^2dy) + y^3(dx) +2xdy + 2ydx = 0

dy (3xy^2+2x) = -dx (y^3+2y)

dy/dx = -(y^3+2y)/(3xy^2+2x)

I assume you mean the point (3,1)

x = 3

y = 1

so

m = dy/dx = -(1+2)/(9+6) = - 3/15 = -1/5

put in point

1 = m * 3 + b

1 = -3/5 + b

b = 8/5

y = -x/5 + 8/5

5y = 8-x

**Answer this Question**

**Related Questions**

COLLEGE CALCULUS. - Use implicit differentiation to find the equation of the ...

math - Use implicit differentiation to find the equation of the tangent line to ...

calculus - Use implicit differentiation to find an equation of the tangent line ...

Calculus - Use implicit differentiation to find the slope of the tangent line to...

Calculus - I am unsure of how to take the derivative of this equation. It may be...

Calculus - Use implicit differentiation to find an equation of the tangent line ...

Calculus - Use implicit differentiation to find an equation of the tangent line ...

Calculus - Use implicit differentiation to find an equation of the tangent line ...

calculus - use implicit differentiation to find an equation of the tangent line ...

Calculus - Use implicit differentiation to find the slope of the tangent line to...